2017
DOI: 10.1007/s00134-017-4791-3
|View full text |Cite
|
Sign up to set email alerts
|

Critical illness: the brain is always in the line of fire

Abstract: Life-threatening systemic insults or diseases often affect the brain. In critically ill patients, acute brain dysfunction manifests in several ways including reduced consciousness, coma, or delirium. The pathophysiology is complex, incompletely understood, and may relate to critical illness-related inflammatory changes, neurotransmitter imbalances, or failure of adequate energy substrate delivery [1], as well as to the applied treatments, pharmacological neurotoxicity, or the hostile ICU environment (Fig. 1) [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 17 publications
0
9
0
2
Order By: Relevance
“…Research indicates that a regular nutritional evaluation using antropometric and the biochemical analysis are complicated in critical patients due to weight loss, dehydration, and edema [31]. Additionally, the pharmacological therapy with opioids, benzodiazepnics, and insulin for the treatment of physiological changes (pain, agitation, anxiety, and metabolic disorders) and to minimize external factors such as noise, often contribute to higher mortality rates in the ICU [32].…”
Section: Discussionmentioning
confidence: 99%
“…Research indicates that a regular nutritional evaluation using antropometric and the biochemical analysis are complicated in critical patients due to weight loss, dehydration, and edema [31]. Additionally, the pharmacological therapy with opioids, benzodiazepnics, and insulin for the treatment of physiological changes (pain, agitation, anxiety, and metabolic disorders) and to minimize external factors such as noise, often contribute to higher mortality rates in the ICU [32].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have demonstrated that injury to the blood-brain barrier (BBB) plays a key role in the pathophysiological mechanism of SAE (3,4). Annane and Sharshar (3) demonstrated that interventions targeting the blood-brain barrier have shown promise in prevention of cognitive dysfunction in various experimental models of sepsis.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, patients presenting electrographic seizures tended to have lower MMSE level prior to surgery, though this did not reach statistical significance. Both age and preexisting cognitive impairment are well-known risk factors for delirium in ICU patients [13]. It should be discussed whether both entities-seizures and deliriummay be independent consequences of major surgery on an aged and potentially already impaired brain.…”
Section: Discussionmentioning
confidence: 99%